Severe Acute Respiratory Syndrome Coronavirus 2 Normalized Viral Loads and Subgenomic RNA Detection as Tools for Improving Clinical Decision Making and Work Reincorporation. (30th July 2021) - Santos Bravo, Marta; Nicolás, David; Berengua, Carla; Fernandez, Mariana; Hurtado, Juan Carlos; Tortajada, Marta; Barroso, Sonia; Vilella, Anna; Mosquera, Maria Mar; Vila, Jordi; Marcos, María Angeles
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse-transcription polymerase chain reaction (RT-PCR) provides a highly variable cycle threshold (Ct) value that cannot distinguish viral infectivity. Subgenomic ribonucleic acid (sgRNA) has been used to monitor active replication. Given the importance of long RT-PCR positivity and the need for work reincorporation and discontinuing isolation, we studied the functionality of normalized viral loads (NVLs) for patient monitoring and sgRNA for viral infectivity detection. Methods: The NVLs measured through the Nucleocapsid and RNA-dependent-RNA-polymerase genes and sgRNA RT-PCRs were performed in 2 consecutive swabs from 84 healthcare workers. Results: The NVLs provided similar and accurate quantities of both genes of SARS-CoV-2 at 2 different timepoints of infection, overcoming Ct-value and swab collection variability. Among SARS-CoV-2-positive samples, 51.19% were sgRNA-positive in the 1st RT-PCR and 5.95% in the 2nd RT-PCR. All sgRNA-positive samples had >4 log10 RNA copies/1000 cells, whereas samples with ≤1 log10 NVLs were sgRNA-negative. Although NVLs were positive until 29 days after symptom onset, 84.1% of sgRNA-positive samples were from the first 7 days, which correlated with viral culture viability. Multivariate analyses showed that sgRNA, NVLs, and days of symptoms were significantly associated ( P  < .001). Conclusions: The NVLs and sgRNA are 2 rapid accessible techniques that could be easily implemented in routine hospital practice providing a useful proxy for viral infectivity and coronavirus disease 2019 patient follow-up. Abstract : SARS-CoV-2 normalized viral loads and sgRNA detection are 2 rapid accessible tools that overcome Ct value and respiratory sample collection variability. They could be easily implemented in routine hospital practice providing a useful proxy for infectivity and COVID-19 patient follow-up.